Detection of Immunotherapeutic Response in a Transgenic Mouse Model of Pancreatic Ductal Adenocarcinoma using Multi-parametric MRI Radiomics: A Preliminary Investigation - Eresen, Aydin (Acad Radiol, 2020)
RATIONALE AND OBJECTIVES: To develop classification and regression models interpreting tumor characteristics obtained from structural (T1w and T2w) MRI data for early detection of dendritic cell (DC) vaccine treatment effects and prediction of long-term outcomes for LSL-Kras(G12D);LSLTrp53(R172H);Pdx-1-Cre(KPC) transgenic mice model of pancreatic ductal adenocarcinoma(PDAC). MATERIALS AND METHODS: Eight mice were treated with DC vaccine for three weeks while eight KPC mice were used as untreated control subjects. The reproducibility of the computed 264 features was evaluated using the intra-class correlation coefficient. Key variables were determined using a three-step feature selection approach. Support vector machines classifiers were generated to differentiate treatment-related changes on tumor tissue following 1(st) and 3(rd) weeks of the DC vaccine therapy. The multivariable regression models were generated to predict overall survival (OS) and histological tumor markers of KPC mice using quantitative features. RESULTS: The quantitative features computed from T1w MRI data has better reproducibility than T2w MRI features. The KPC mice in treatment and control groups were differentiated with a longitudinally increasing accuracy (1(st) and 3(rd) weeks: 87.5% and 93.75%). The linear regression model generated with five features of T1w MRI data predicted OS with an RMSE <6 days. The proposed multivariate regression models predicted histological tumor markers with relative error <2.5% for fibrosis percentage (RMSE: 0.414), CK19(+) area (RMSE: 0.027), and Ki67(+) cells (RMSE:0.190). CONCLUSION: Our results demonstrated that proposed models generated with quantitative MRI features can be used to detect early treatment-related changes in tumor tissue and predict OS of KPC mice following DC vaccination.